Prospective Evaluation of Rate of Hindfoot/Ankle Fusion with Augment Injectable Bone Graft - Jacob Priester MD; Christopher D. Kreulen MD; Phillip J. Shaheen MD; Eric Giza MD; Samuel Simister MD (Foot & Ankle Orthopaedics)
Category: Hindfoot; Ankle Introduction/Purpose: Augment ® Bone Graft is a mixture of rhPDGF-BB, beta-TCP and bovine collagen which has received FDA approval for use as a substitute for autografts during hindfoot and/or ankle arthrodesis. Although a recent meta analysis demonstrated that the rhPDGF-BB and beta-TCP mixture has comparable CT fusion rates and radiographic union rates to those of autografts, these studies excluded patients with prior joint site arthrodesis. In our study, we specifically use Augment ® Injectable Bone Graft (AIBG) which has only very recently received labeling change approval. The goals of our study are to assess fusions rates in patients who receive AIBG during hindfoot and/or ankle arthrodesis, and then subsequently compare fusion rates between primary vs. revision hindfoot and/or ankle arthrodesis as primary outcomes. Methods: We prospectively enrolled patients aged 18-85 who underwent subtalar, calcaneocuboid, talonavicular, and/or ankle arthrodesis from one of two academic surgeons including both primary and revisions fusions. The patients received AIBG and were excluded if any other graft material was used. Demographic data and patient reported outcomes were collected preoperatively and at follow-up visits including Visual Analog Pain Scale (VAS), Foot Function Index (FFI), Foot and Ankle Ability Measure (FAAM) Sports Subscale, and Veterans Rand 12 (VR-12) physical and mental subscores. Patients were followed at 2 weeks, 6 weeks, 3 months, 6 months, 1 year, and 2 years postoperatively. The primary outcome measure was fusion rate via CT scan at 4 months with secondary outcomes consisting of the patient reported outcome data and rate of revisions. Results: 62 patients met inclusion criteria, 50 patients had a 4-month postoperative CT scan to assess for fusion with 78% of the CT scans (39 out of 50) demonstrating fusion at that time. There were only 3 revision fusion patients, with 1 of the 3 failing to fuse. 54 of the patients were followed through their 6 month visits, 44 patients through 1 year, and 24 patients were seen for their 2-year follow-up visit. All patient reported outcomes demonstrated improvement from preoperatively to final follow-up with VAS, FFI, FAAM, and VR12 showing statistically significant improvement. Conclusion: This prospective study demonstrates that Augment ® Injectable Bone Graft is an acceptable alternative to allograft for either primary or revision hindfoot arthrodesis procedures with 78% of patients achieving fusion on a 4-month postoperative CT scan and with steady noted improvement in multiple validated patient-reported outcome measures. Long term follow up data is being collected.